SINTESIS METIL ESTER ASAM LEMAK DARI MINYAK KELAPA HASIL PEMANASAN - Rorong, Johnly; Aritonang, Henry F.; Ranti, Ferdinan P. (Sam Ratulangi University, 2008)
A research has been done to synthesis mixed fatty acid esther from coconut oil, before and after heating with variation time 1, 2 and 3 hours at ±175-180 ºC. The synthesis was done with transestherification method using acid as a cathalyst at 65 °C. The transestherification result was analyzed using gas chromatography to obtain its fatty acid composition. The mass of FAME obtained from methyl esther synthesized from coconut oil with heating time 0, 1, 2 and 3 hours are; 94.73 g, 93.57 g, 95.76 g dan 93.88 g respectively.